The knife's edge: Masculinities and precarity in East Africa. (August 2020) - Fast, Danya; Bukusi, David; Moyer, Eileen
Abstract: In our field sites and clinical practice in East Africa, we regularly encounter men who have become overwhelmed by "thinking too many thoughts" and "gone crazy from confusion, " brought about by the problems of life created by deepening social, economic and political precarity. Across diverse settings, many African men continue to be enmeshed in social and material obligations and expectations that position them as economic consumers and providers for those they care for and love. When these gendered obligations, expectations and fantasies are left unfulfilled, this sense of failure can be embodied to produce particular kinds of health effects. Namely, men may become plagued by troublesome and confusing thoughts, leading them in some cases to "give up on" (as our research subjects put it) pursuing work and education, to become immersed in problematic drug and alcohol use, and even to take their own lives. While these afflictions can be glossed using the language of depression, anxiety, addiction and suicide, such medicalizing frames may obscure more nuanced social, structural and affective diagnoses of what is happening to men across Africa and globally. Anthropology provides us with alternative frames through which to understand how psychological wounds are made—and healed. Highlights: Experiences of stagnation threaten the mental health of East African men. Faced with the problem of stagnation, many men pursue a social-spatial "fix". Places of work and leisure provide men with a valued sense of momentum. Substance use and even suicide can open up new relationships to time. Interventions must look beyond questions of pathology, access and stigma.